Pemeriksaan urine sederhana pada wanita usia subur di Tahoku, Negeri Hila - Mus, Rosdiana; tamalsir, Dylan tamalsir; Abbas, Mutmainnah; Asmin, Elpira; Astuty, Eka; Yunita, Melda; Esmeraldine, Genevieva; Mailoa, joice; Putrie, intania Riska; Agustina, Titin (Jurnal PADE: Pengabdian & Edukasi, 2024)
Routine medical check up as part of preventive and Germas. Early and simple test  using urine samples to prevent Urinary Tract Infections (UTI) in women of reproductive age can be a preventive. Markers of UTI  in urine test by dipstick method are leukocytes and nitrites. This test is a simple that can use at a health service. The aim of this community service activity is to carry out a simple urine test for Women reproductive Age in Tahoku. The method of implementing activities is divided into 3 stages, namely preparation, implementation and evaluation of activities. The location of the activity was in Negeri Hila, one of the areas on Ambon Island. An initial survey at the Hila Care Community Health Center found that community visits very low. This is due to the low level of public interest in carrying out regular test to maintain health status. Urine examinations use the dipstick method. The results of community service activities involving 31 participants, with the majority of participants aged <25 years with positive urine leukocyte examination results of 80.6% and positive urine nitrites of 100%. These results indicate that most of the subjects have signs of UTI symptoms. The results of this service are used as information for local health services to increase public awareness to care about health and to carry out periodic health checks to prevent disease.